The Recognition, Utilization Rates, Barriers, and Application Accuracy of the Hamstring Strain Clinical Practice Guidelines - Edward Mulligan; Liana Wooten; Tara Dickson; Eric Hegedus; Benjamin Stern (International Journal of Sports Physical Therapy)
# Background and Purpose